Storytelling in English Language Learning: Boosting Confidence and Discourse in EFL Contexts - Rahmawati, Acce; Suhatmady, Bibit; Sucahyo, Didik; Hermagustiana, Istanti (Borneo Educational Journal (Borju), 2025)
This study investigates the role of storytelling as a teaching strategy for improving English language abilities among vocational students at SMKN 1 Samarinda. Recognizing a void in the literature on practical approaches for reducing speaking anxiety in EFL contexts, this study analyzes students’ perspectives of how storytelling impacts their confidence, discourse growth, and engagement. Data were acquired using a phenomenological technique via semi-structured interviews with three selected students, with validation provided by insights from their English teacher to increase the study’s credibility. The main findings show that storytelling boosts students’ confidence in speaking, promotes discourse expansion, and encourages active engagement in classroom activities. However, some challenges emerged, such as nervouness when presenting stories and concerns about peer evaluation. These elements occasionally prevented pupils from fully participating. The conclusion indicates that storytelling can be an effective method for creating a more participatory and encouraging language learning environment. Educators are advised to add narrative activities designed to reduce fear and improve confidence, allowing children to practice speaking abilities in a comfortable environment.